2020
DOI: 10.21511/imfi.17(1).2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Application of an intangible asset valuation model using panel data for listed enterprises in Vietnam

Abstract: Intangible assets play an important role in increasing the value of companies. The performance of companies increasingly depends on ideas, information, and professional services rather than tangible assets. The question of how to accurately measure intangible assets remains a challenge for many scientists. This study aims to measure intangible assets of 396 companies listed on Vietnam’s stock market between 2010 and 2014 using the panel data technique by Yamayuchi (2014). The estimation shows that intangible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Building on this, we demonstrate that intangibles are also linked to improved access to capital resources, which could be one of the key mechanisms that strengthens the competitive advantages of SMEs and helps them achieve better performance. Our findings thus echo Quan et al (2020) who, also in the context of Vietnam, estimate that intangible assets increasingly make up a large share of companies' total assets, and that intangible assets exert a positive impact on improving company capability of obtaining external sources of fund.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Building on this, we demonstrate that intangibles are also linked to improved access to capital resources, which could be one of the key mechanisms that strengthens the competitive advantages of SMEs and helps them achieve better performance. Our findings thus echo Quan et al (2020) who, also in the context of Vietnam, estimate that intangible assets increasingly make up a large share of companies' total assets, and that intangible assets exert a positive impact on improving company capability of obtaining external sources of fund.…”
Section: Discussionsupporting
confidence: 83%
“…Second, the secondary markets for trading intangible assets (e.g. trademarks, franchises, copyrights) is starting to develop in Vietnam (Quan et al, 2020). Therefore, banks may find it feasible to liquidate the intangible assets that firms have pledged as collateral in the event of payment default.…”
Section: Table 3 Reports the Estimated Results Using A Bivariate Prob...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study by Binh et al (2020) showed that intangible assets of enterprises, which are the basis and at the same time the result of innovative activities of companies, have a positive impact on increasing the efficiency of enterprises and increasing their market value. At the same time, there is no general approach to assessing the value of intangible resources as objects of management influence, especially those that cannot be accurately identified in the accounting and financial statements of a business entity as intangible assets.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…In most studies, three main approaches to the valuation of intangible assets are distinguished: cost, income and market approaches (Binh et al 2020;Pastor et al, 2017;Salamudin et al, 2010).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%